Nonparametric instrumental variable estimation under monotonicity - Denis Chetverikov; Daniel Wilhelm (Centre for Microdata Methods and Practice (cemmap), 2016)
The ill-posedness of the inverse problem of recovering a regression function in a nonparametric instrumental variable (NPIV) model leads to estimators that may suffer from poor statistical performance. In this paper, we explore the possibility of imposing shape restrictions to improve the performance of the NPIV estimators. We assume that the regression function is monotone and consider sieve estimators that enforce the monotonicity constraint. We define a restricted measure of ill-posedness that is relevant for the constrained estimators and show that under the monotone IV assumption and certain other conditions, our measure of ill-posedness is bounded uniformly over the dimension of the sieve space, in stark contrast with a well-known result that the unrestricted sieve measure of ill-posedness that is relevant for the unconstrained estimators grows to infinity with the dimension of the sieve space. Based on this result, we derive a novel non-asymptotic error bound for the constrained estimators. The bound gives a set of data-generating processes where the monotonicity constraint has a particularly strong regularization effect and considerably improves the performance of the estimators. The bound shows that the regularization effect can be strong even in large samples and for steep regression functions if the NPIV model is severely ill-posed a finding that is confirmed by our simulation study. We apply the constrained estimator to the problem of estimating gasoline demand from U.S. data.
Keywords: 330